Circularly Polarized High Harmonics in Argon: Dipole and Non-Dipole Effect - Alp, Dılan; Candan, İlhan (My University, 2023)
The interaction of the intense laser pulse, which forms the basis of the strong laser field and non-linear optical physics, with atoms, molecules, and solids leads to the High Order Harmonic Generation (HHG). There are many theoretical and experimental research related to this process defined by the Semi-Classic Model which is called the Three Step Model. In this article, the dipole and non-dipole effects specified in the theoretical Lewenstein model to be used in the Argon atom interacting with the strong circular laser field (800nm) and the resulting higher order harmonic spectrum will be investigated. We compared the results obtained using the non-collinear beams with opposite circular polarizations with those obtained using a single circularly polarized beam or a linearly polarized beam. It could be said that the circular polarization can significantly affect the HHG process in an argon atom exposed to a laser field with 800 nm wavelength and 1015 W/cm2 intensity.
Keywords: Argon; high harmonic generation; dipole; non-dipole